Quem são os “senhores da guerra” a complexa relação entre corporações, estado e guerra - (:unkn) unknown (Universidade Federal do Pampa, 2014)
The present work analyses the actual influence the large corporations exert on the elaboration and the execution of the States’ foreign policy, especially in the United States of America (USA). Thus, it exposes how wide the degree of expressivity, influence and autonomy of the United States and the corporations is, considering the Shifts suffered by the international scenery, Therefore, it is subjected to scrutiny how the Lobbies and the Thinks Tanks, important tools of the large corporations, act and influence on the American Congress so that the foreign policy also serves their interests. Due to the transformations verified throughout the international system from the September, 11th 2001 attacks on, George W. Bush (20012009) and Barack Obama’s (2009- ) governments are taken as a pattern for analysis. The Afghanistan war (2001) and the Iraq war (2003) are analysed to demonstrate the amount of the military expenses incurred by the USA and whether, in fact, those military actions would be convenient for the State.
Keywords: International relations; United States of America; American foreign policy; Weapons; Lobby; Relações internacionais; Política externa americana; Armas; Estados Unidos da América